Integrating STEM and Environmental Education: Effects On Student Attitudes and Knowledge - Zainal Abidi; Annisa Risma Arianti; Yudha Hanika Anggriawan (International Journal of Mathematics and Science Education, 2024)
This paper investigates the integration of Science, Technology, Engineering, and Mathematics (STEM) with Environmental Education (EE) and its impact on students' environmental attitudes and knowledge. The study involved 300 students who participated in a curriculum that merged STEM concepts with environmental issues. Findings showed improved environmental awareness and a more positive attitude toward conservation practices among students. The study highlights the importance of interdisciplinary approaches in fostering both scientific literacy and environmental responsibility.